2009
DOI: 10.1021/jp9090975
|View full text |Cite
|
Sign up to set email alerts
|

Laser Spectroscopy of Conformationally Constrained α/β-Peptides: Ac-ACPC-Phe-NHMe and Ac-Phe-ACPC-NHMe

Abstract: Single-conformation ultraviolet and infrared spectra have been recorded under the isolated molecule conditions of a supersonic expansion for three conformationally constrained alpha/beta-peptides, Ac-L-Phe-ACPC-NHMe (alpha(L)beta(ACPC)), Ac-ACPC-L-Phe-NHMe (beta(ACPC)alpha(L)), and Ac-ACPC-D-Phe-NHMe (beta(ACPC)alpha(D)). These three molecules are close analogues of the hAla-containing alpha/beta-peptide counterparts Ac-L-Phe-beta(3)-hAla-NHMe, Ac-beta(3)-hAla-L-Phe-NHMe, and Ac-beta(3)-hAla-D-Phe-NHMe, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…Such investigations of isolated peptides in the gas phase offer an unbiased view of structure-formation trends intrinsic to the molecule, a strategy that is successful for charged and uncharged amino acids and peptides. [20][21][22][23][24][25][26][27][28][29][30] By the stepwise addition of perturbing contributions, in this case, the presence of cations, we aim to determine the main contributions to protein secondary structure formation in a bottom-up approach. The success of such an approach is critically linked to the quality of the description of the potential-energy surface of the system under investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such investigations of isolated peptides in the gas phase offer an unbiased view of structure-formation trends intrinsic to the molecule, a strategy that is successful for charged and uncharged amino acids and peptides. [20][21][22][23][24][25][26][27][28][29][30] By the stepwise addition of perturbing contributions, in this case, the presence of cations, we aim to determine the main contributions to protein secondary structure formation in a bottom-up approach. The success of such an approach is critically linked to the quality of the description of the potential-energy surface of the system under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown similar behavior owing to conformational ensembles for peptides in the gas phase at finite temperature. [22][23][24][25][26][27] Furthermore, the energy differences of the low free-energy conformers lie within the uncertainty of the employed method, as discussed in the section called Benchmarks below. Consequently, an ensemble of conformations is assumed.…”
Section: Wwwchemeurjorgmentioning
confidence: 93%
“…Vibrational couplings make the interpretation less easy, and confident assignments rely on a large spectral range (the whole amide I-III regions), especially when spectral resolution is limited, usually 1% of the IR frequency for a freeelectron source [48,54,55,66,69,79,80,82,83,95,97,105,108,131,132,136,141,142]. Difference frequency generation from table-top OPOs [52,64,90,104,120,126,127,137,139,144,145] has become a valuable alternative source to FELs, providing spectral resolutions in the cm À1 range, and solid conformational assignments have emerged from studies combining amide I/II and amide A spectral ranges (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the folding from the NH of the second Ala residue into a C7 H-bond is hampered by significant entropic effects which favour extended forms because of their multiple low frequency modes. Amidated models, [63,70,73,83,114] as well as di-or tri-peptides with Phe or Trp as first residue [84,85,94,104,112], have also revealed C5-containing secondary structures. In these conformations, the C5 H-bond occurring at the aromatic residue is additionally stabilised by an interaction between the π system of the aromatic ring and the NH of the following residue along the chain , making the 5-π motif very common among these secondary structures.…”
Section: C5 Interactions a Signature Of Extended β-Strand-likementioning
confidence: 99%
See 1 more Smart Citation